Socio-Legal Perspective on Renewing the Law Order In New Normal Situation of Covid-19 Pandemic - Yusriyadi1 , Aditya Yuli Sulistyawan2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Covid-19 pandemic is a reality that has a big impact on all aspects of people’s lives, whether economic,social, cultural, or legal elements. In the face of this extraordinary situation, social change becomes aninevitable necessity. However, this big challenge is not something that is easy to deal with. Various problemsin the community arise and become anxious together as a nation. Through this study, an understanding isobtained that to face the Covid-19 pandemic situation in the midst of this new normal order, to deepen therole of Indonesian social capital of Pancasila. The study of legal sociology is deemed capable of revealinglegal reality, social changes in the pandemic era and how we renew law in the middle of a pandemic will bewell read and produce good judicial choices in the midst of Covid-19 pandemic.